2005
DOI: 10.2337/diabetes.54.5.1297
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations of Fatty Acid and Glycerol Release From Human Subcutaneous Adipose Tissue In Vivo

Abstract: We sought evidence for pulsatility of lipolysis in human subcutaneous adipose tissue in vivo. Arterialized and adipose tissue venous blood samples were drawn at 2-min intervals from nine healthy subjects. This procedure was repeated during hyperinsulinemic-euglycemic clamp to remove insulin pulsatility. We found evidence for pulsatile release of both nonesterified fatty acids (NEFAs) (seven of nine subjects) and glycerol (five of six subjects) with a period of ϳ12-14 min. This pulsatility was maintained even d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Leptin secretion falls in early starvation (23), and there is evidence for pulsatile secretion of adiponectin and leptin (16). Pulsatile release of other hormones such as insulin and glucagon (18,25) and of products of lipolysis from adipose tissue in vivo (21), with periods of 10 -15 min, have also been reported. The pulsatile release of an adipokine would compromise the steady-state assumption necessary for our calculation of the secretion rate.…”
Section: Discussionmentioning
confidence: 95%
“…Leptin secretion falls in early starvation (23), and there is evidence for pulsatile secretion of adiponectin and leptin (16). Pulsatile release of other hormones such as insulin and glucagon (18,25) and of products of lipolysis from adipose tissue in vivo (21), with periods of 10 -15 min, have also been reported. The pulsatile release of an adipokine would compromise the steady-state assumption necessary for our calculation of the secretion rate.…”
Section: Discussionmentioning
confidence: 95%
“…97,98 Release from AT of the products of lipolysis is pulsatile in dogs 99 and in humans. 100 In vivo studies based on the use of tracer methodology have clearly shown that lipolytic activity is greater in upper-body subcutaneous than in leg AT (per kg of fat) in lean and obese men and women.…”
Section: Recent Discoveries In Mechanisms Involved In the Control Of mentioning
confidence: 99%
“…Furthermore, differences in tissue perfusion and possibly also in FFA extraction and/or uptake, e.g., between individual skeletal muscles [58,59], likely lead to disproportionate distribution of total FFA flux amongst fat-free tissues or different adipose tissue regions, and therefore further confound the interpretation of ratios. It is also important to note that, probably due to the pulsatile/oscillatory nature of adipose tissue lipolysis [60,61], the intra-individual day-to-day variability of plasma FFA turnover rates is considerable, ∼15-30% [62-64]. Therefore, careful attention to details and standardization of the experimental conditions (prior diet and physical activity, fasting duration, sample timing, etc.)…”
Section: Systemic Plasma Ffa Availabilitymentioning
confidence: 99%